2000
DOI: 10.1103/physreve.61.6538
|View full text |Cite
|
Sign up to set email alerts
|

Learning dynamics from nonstationary time series: Analysis of electroencephalograms

Abstract: We propose an empirical modeling technique for a nonstationary time series analysis. Proposed methods include a high-dimensional (N>3) dynamical model construction in the form of delay differential equations, a nonparametric method of respective time delay calculation, the detection of quasistationary regions of the process by recurrence analysis in the space of model coefficients, and final fitting of the model to quasistationary segments of observed time series. We also demonstrate the effectiveness of our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 11 publications
0
19
0
2
Order By: Relevance
“…From the dynamical point of view, abnormality of cracks in concrete dams mainly means that the dam state in the phase space no longer tends to the original attractor but to a new one because of the evolution of internal dynamical structure or large external disturbance. In addition, it is generally supposed that a significant change in dynamical structures can be reflected in the observation sequence of relevant variables [10]. The exponent method of dynamical cross-correlation factor to diagnose abnormality of cracks in concrete dams is proposed based on the thought of exponent of dynamical correlation factor [11][12][13] in the paper.…”
Section: Abnormality Diagnosis Methods Of Cracks In Concrete Damsmentioning
confidence: 99%
“…From the dynamical point of view, abnormality of cracks in concrete dams mainly means that the dam state in the phase space no longer tends to the original attractor but to a new one because of the evolution of internal dynamical structure or large external disturbance. In addition, it is generally supposed that a significant change in dynamical structures can be reflected in the observation sequence of relevant variables [10]. The exponent method of dynamical cross-correlation factor to diagnose abnormality of cracks in concrete dams is proposed based on the thought of exponent of dynamical correlation factor [11][12][13] in the paper.…”
Section: Abnormality Diagnosis Methods Of Cracks In Concrete Damsmentioning
confidence: 99%
“…The reason lies in the evolution of internal dynamical structure or large external disturbance. In addition, it is generally supposed that a significant change in dynamical structure can be reflected in the observed sequence of relevant variables [3]. Therefore, dynamical properties of the observed sequence can be used to analyze the dynamical behavior of an actual dam.…”
Section: Introductionmentioning
confidence: 99%
“…This type of analysis has been applied in several studies of EEG signals. For instance, quantitative characteristics of segmental organization of the brain signals were explored in resting state EEG [14], [15]. Another study reported differences in the duration of stationary EEG segments between patients with mild Alzheimer's disease and healthy subjects [16].…”
Section: Introductionmentioning
confidence: 99%